Principles and methods of teaching - Zulueta, Francisco M. (Mandaluyong City, 2006)
This book is intented primarily for students in the College of Education, and beginning teachers, to have a strong foundation and a through grasp on concepts, theories, principles and teaching-learning process
Keywords: Teaching methods; Teaching principles